The efficacy and safety of a taxane-based chemotherapy regimen combined with a PD-1 inhibitor in HNSCC: a multicenter real-world study - Min Ouyang; Hanquan Sun; Xiaoyu Liu; Haijun Wu; Feilong Deng; Erdong Shen; Guozheng Peng; Hanbing Wu; Yinshan Zhao; Hui Xiong; Bin Liu; Shasha He; et al. (World Journal of Surgical Oncology)
Abstract Objective This study aims to elucidate the therapeutic efficacy and safety of a taxane-based chemotherapy in combination with immune checkpoint inhibitors regimen in patients diagnosed with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). Methods We retrospectively collected clinical data from 154 patients who received at least two cycles of PD-1 inhibitors in combination with a taxane-based chemotherapy as first-line treatment in seven hospitals in Hunan Province, between December 2018 and December 2023. These patients were subjected to long-term follow-up. Results The study included 154 eligible patients, with a median follow-up period of 21.5 months. The median PFS was 8.7 months, while the median OS was 16.7 months. The 12-month PFS rate was 43.6%, and the 12-month OS rate was 60.1%. At 24 months, the PFS rate was 34.4%, and the OS rate was 36.9%. With 26 complete responses (16.9%) and 52 partial responses (33.8%), the ORR was 50.6%. Stable disease was observed in 54 patients (35.1%), resulting in a disease control rate of 85.7%, while 22 patients showed progressive disease. In the univariate analysis, the distant organ metastasis had a statistically significant impact on both PFS and OS. Subsequent radiotherapy following this protocol also showed a statistically significant effect on PFS and OS. However, radiotherapy before recurrent metastasis did not significantly affect PFS, though it did have a significant impact on OS. Other factors analyzed did not show a statistically significant effect on PFS and OS. Multivariate analysis indicated that the distant organ metastasis and subsequent radiotherapy following this protocol were independent prognostic factors for PFS in patients with R/M HNSCC, and the latter was also an independent prognostic factor for OS in these patients. Regarding safety, during treatment anemia was observed in 97 patients, leukopenia in 64, neutropenia in 33, thrombocytopenia in 28, transaminase elevation in 46, hypothyroidism in 46 patients, and one patient stopped taking the medication due to a serious adverse reaction. No treatment-related deaths occurred. Conclusion The combination of PD-1 inhibitors with a a taxane-based chemotherapy regimen as a first-line treatment for R/M HNSCC patients demonstrates good therapeutic efficacy and acceptable safety profiles.